Match Quality, Worker Productivity, and Worker Mobility: Direct Evidence from Teachers - Jackson, C. Kirabo (The Review of Economics and Statistics, 2013)
I investigate the importance of the match between teachers and schools for student achievement. I show that teacher effectiveness increases after a move to a different school and estimate teacher-school match effects. Match quality explains away a quarter of and has two-thirds the explanatory power of teacher quality. Match quality is negatively correlated with school switching, is unrelated to exit, and increases with experience. This paper provides the first estimates of worker-firm match quality using output data, as opposed to inferring productivity from wages or employment durations. The results suggest that workers seek high-quality matches for reasons other than higher pay.